Nafkah Iddah After Divorce Hadith Perspective - Silviana; Zulkifli; Jumni Nelli (Yayasan Cendekia Gagayunan Indonesia, 2024)
Alimony in this form is obligatory based on the Qur'an, the Sunnah and the consensus of scholars. When the two couples are both adults, it is the husband's obligation to provide food, clothing and housing for his wife and children in accordance with the social status of the couple and in accordance with the customs of the community in their place of residence. Iddah maintenance is everything that the husband gives to his divorced wife in the form of clothing, food and shelter. The time of giving alimony is during the iddah period and if the ex-wife has visited her iddah period, it means that the responsibility of the husband who provides alimony is over. The research on